Experimental study of RCCI combustion and load extension in a compression ignition engine fueled with gasoline and PODE. (1st October 2016) - Tong, Laihui; Wang, Hu; Zheng, Zunqing; Reitz, Rolf; Yao, Mingfa
Highlights: Controllable RCCI could be achieved using PODE as the DI high reactivity fuel. Soot free combustion with PODE regardless of premixed ratio and DI timing. 1.76 MPa IMEP load can be obtained using PODE with single injection strategy. Ultra-low smoke and NOx are achievable with stoichiometric gasoline/PODE RCCI operation. Abstract: An experimental investigation has been conducted to explore the effects of polyoxymethylene dimethyl ethers (PODE) as the direct-injection (DI) high reactivity fuel in dual-fuel reactivity controlled compression ignition (RCCI) operation on a single-cylinder, heavy-duty diesel engine. The combustion and emission characteristics, together with the combustion phasing controllability of gasoline/diesel and gasoline/PODE RCCI operation are compared and discussed. The results show that stable and controllable RCCI operation is obtainable using PODE as the DI high reactivity fuel. Improved indicated thermal efficiency (ITE) and ultra-low smoke can be achieved with PODE, with a slight penalty, but still comparable NOx emissions. The maximum load of gasoline/PODE operation could be extended to 1.76 MPa indicated mean effective pressure (IMEP) with a single injection strategy, which is significantly higher than that of gasoline/diesel operation with an optimized double-injection strategy (1.39 MPa IMEP), while still maintaining ultra-low smoke and comparable ITE and PPRR. Stoichiometric and clean gasoline/PODE dual-fuel RCCI operation was also achievable at high load. This enables the possibility to apply a low-cost three-way catalyst to further reduce the NOx, HC and CO emissions, which offers a very competitive pathway to achieve clean and highly efficient diesel combustion.